Experimental study of high-intensity light channels produced on an extended air path by phase and amplitude modulated femtosecond laser pulses - Apeksimov, Dmitrij V.; Geints, Yuri E.; Matvienko, Gennadij G.; Oshlakov, Viktor K.; Zemlyanov, Alexander A. (Applied optics)
We present the results of our experimental study of the propagation dynamics of high-power femtosecond laser radiation in air with initially imposed amplitude and/or phase modulations. Depending on the modulation type and magnitude, the laser pulse upon nonlinear propagation breaks up into several high-intensity spatially localized light channels, which may or may not contain air plasma and thus are referred to as laser filaments, post-filaments, or plasmaless channels. The pulse modulations are implemented by means of control of the phase or amplitude front using a bimorph deformable mirror or amplitude masks, respectively.We showthat the distance of formation and spatial length of high-intensity light channels along a propagation path strongly depend on the shapes and spatial positions of the inhomogeneities created in the transverse phase/amplitude pulse profile, butweakly depend on their sizes.